Privatization in South Asia : minimizing negative social effects through restructuring - Sub-Regional Workshop on Privatization in South Asia (1999 : Kathmandu, Nepal); Joshi, Gopal; International Labour Organisation. South Asia Multidisciplinary Advisory Team. (New Delhi : South Asia Multidiscipilnary Advisory Team, International Labour Organization, 2000)
Case studies presented at the Workshop on the theme of privatization and restructuring of various public enterprises in South Asian countries.
Includes bibliographical references.
Keywords: Privatization -- South Asia -- Congresses; Government business enterprises -- South Asia -- Congresses